Gal-3BP Negatively Regulates NF-κB Signaling by Inhibiting the Activation of TAK1 - Hong, Chang-Soo; Park, Mi-Ra; Sun, Eun-Gene; Choi, Wonyoung; Hwang, Jun-Eul; Bae, Woo-Kyun; Rhee, Joon Haeng; Cho, Sang-Hee; Chung, Ik-Joo (Frontiers in Immunology, 2019)
Galectin-3-binding protein (Gal-3BP) is a member of the family of scavenger receptor cysteine-rich (SRCR) domain-containing proteins, which are associated with the immune system. However, the functional roles and signaling mechanisms of Gal-3BP in host defense and the immune response remain largely unknown. Here, we identified cellular Gal-3BP as a negative regulator of NF-kB activation and proinflammatory cytokine production in lipopolysaccharide (LPS)-stimulated murine embryonic fibroblasts (MEFs). Furthermore, cellular Gal-3BP interacted with transforming growth factor β-activated kinase 1 (TAK1), a crucial mediator of NF-kB activation in response to cellular stress. Gal-3BP inhibited the phosphorylation of TAK1, leading to suppression of its kinase activity and reduced protein stability. In vivo, we found that Lgals3BP deficiency in mice enhanced LPS-induced proinflammatory cytokine release and rendered mice more sensitive to LPS-induced endotoxin shock. Overall, these results suggest that Gal-3BP is a novel suppressor of TAK1-dependent NF-kB activation that may have potential in the prevention and treatment of inflammatory diseases.